Dissecando o satelitoma de espécies de Drosophila com genomas sequenciados - Leonardo Gomes de Lima (2017)
Satellite DNAs (satDNA) are ubiquitously present in eukaryotic genomes and are usually associated with heterochromatic regions of the genome. Moreover, this genetic element has been recently associated with several biological roles. However, these important genetic elements have been historically neglected and currently there is still a low representativeness of these elements in the databases. In addition, only few studies have focused on a characterization of satDNAs in a phylogenetic context in Drosophila. In this work, we approach this question by performing a de novo characterization of the total set of satDNA sequences (satellitome) present in the genome of 36 Drosophila species. We used the RepeatExplorer pipeline for the de novo identification, as well as alignment, transcription and in situ hybridization analyzes. Herein we described 172 satDNA families, being 133 of them newly described satDNA sequences. Repeat analysis within a phylogenetic framework has revealed the profound divergent nature of satDNA sequences in Drosophila genomes. We observed that the satDNA content varied from 0.54% of D. arizonae genome to 27.4% of D. montana. We confirmed the satDNA library hypothesis evidencing the maintenance of satDNA families shared among closely related species. We also described that the 1.688 satDNA family is present in 13 species of group melanogaster which diverged ~27 Mya, indicating the most striking conservation of a satDNA family in Drosophila. Finally, we found that changes in genome size of Sophophora are positively correlated with transposable element abundance, whereas in Drosophila subgenus satDNA sequences strongly correlate with genome sizevariation.